Lexicographic representation of film discourse - Tursinbayeva Dilbar Ixtiyar qizi (International Journal of Literature and Language Studies, 2026)
Abstract: This article examines the complex interplay between film discourse and modern lexicographic practice, exploring how cinema-related terminology is represented in authoritative dictionaries and how the semantic and pragmatic characteristics of film language are captured in lexical descriptions. The study synthesizes theoretical insights from linguistics, discourse studies and lexicography to illustrate the challenges and innovations in documenting film language. Through dictionary examples and comparison with film discourse phenomena, it foregrounds the semantic richness and pragmatic variability of cinematic terms. The conclusion outlines implications for future dictionary design and discourse analysis.